Hofmeister Effect of Sodium Halides on the Switching Energetics of Thermoresponsive Polymer Brushes. Issue 5 (8th January 2013) - Naini, Crispin Amiri; Thomas, Marc; Franzka, Steffen; Frost, Sven; Ulbricht, Mathias; Hartmann, Nils
Abstract A laser temperature‐jump technique is used to probe the impact of sodium halides on the temperature‐dependent switching kinetics and thermodynamics of poly(N‐isopropylacrylamide) brushes. An analysis on the basis of a two‐state model reveals van't Hoff enthalpy and entropy changes. Sodium halides increase the endothermicity and the entropic gain of the switching process below and above Tc following the Hofmeister series: NaCl > NaBr > NaI. In contrast, enthalpic and entropic changes at Tc remain virtually unaffected. This provides an unprecedented insight into the underlying switching energetics of this classic stimuli‐responsive polymer. Because of its model character, these results represent an essential reference on the way to unpuzzle the molecular driving forces of the Hofmeister effect.